(3x+1)=2 (2x-3)
Me ajuda por favor
Soluções para a tarefa
Respondido por
1
Boa noite JPCH!
![3x + 1 = 2(2x - 3) 3x + 1 = 2(2x - 3)](https://tex.z-dn.net/?f=3x+%2B+1+%3D+2%282x+-+3%29)
![3x + 1 = 4x - 6 3x + 1 = 4x - 6](https://tex.z-dn.net/?f=3x+%2B+1+%3D+4x+-+6)
![3x - 4x + 1 = - 6 3x - 4x + 1 = - 6](https://tex.z-dn.net/?f=3x+-+4x+%2B+1+%3D++-+6)
![3x - 4x = - 6 - 1 3x - 4x = - 6 - 1](https://tex.z-dn.net/?f=3x+-+4x+%3D++-+6+-+1)
![- x = - 6 - 1 - x = - 6 - 1](https://tex.z-dn.net/?f=+-+x+%3D++-+6+-+1)
![- x = - 7 - x = - 7](https://tex.z-dn.net/?f=+-+x+%3D++-+7)
![x = 7 x = 7](https://tex.z-dn.net/?f=x+%3D+7)
Espero ter ajudado!
Espero ter ajudado!
Respondido por
0
Olá...
(3x + 1) = 2(2x - 3)
3x + 1 = 4x - 6
3x - 4x = - 6 - 1
- x = - 7 →(× por -1)
x = 7
Resposta: x = 7
Espero ter ajudado.
Perguntas interessantes
Matemática,
10 meses atrás
Português,
10 meses atrás
Inglês,
10 meses atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás